The roles of a MiRNA and its targeted methyltransferase 3 in carotenoid accumulation in adductor muscles of QN orange scallops - Junlin Song; Xiao Sun; Chunde Wang (BMC Genomics)
Abstract Background QN Orange scallops are interspecific hybrids with orange adductor muscles that are rich in carotenoids. In this study, analysis of miRNA expression profiles was performed to explore possible regulatory patterns involved in carotenoid accumulation in adductor muscles of QN Orange scallops. Results A total of 91 differentially expressed miRNA between the white and orange adductor muscles were identified. GO and KEGG analysis of target genes of differentially expressed miRNAs revealed enrichments in the transmembrane transporter activity-related pathways, kinase activity-related pathways, signal transduction-related pathways, ATP binding cassette transporters (ABC transporters), retinol metabolism, lipid-related metabolism, and calcium signaling pathway. In particular, miRNA Contig1462_36180, which was shown to negatively regulate the activity of methyltransferase 3 (METTL3) by dual-luciferase reporter assay, may play a pivotal role in the accumulation of carotenoids. Furthermore, METTL3 interference seemed to reduce the pectenoxanthin content and m6A level. Conclusion It is thus speculated that Contig1462_36180 may regulate m6A methylation by regulating METTL3, which in turn affects pectenoxanthin accumulation in QN Orange scallops.